Attitudes towards sex: a comparison of prisoners and the general community - Malacova, Eva; Butler, Tony; Richters, J.; Yap, L.; Grant, L.; Richards, A.; Smith, A.; Donovan, B. (CSIRO Publishing, 2011)
Background: National population surveys of attitudes towards sexual issues typically exclude prisoners and little is known about their attitudes compared with the community. Methods: Using computer-assisted telephone interviews, we compared a representative sample of 2289 prisoners (men = 1960, women = 329), aged 18–59 years, from two Australian states against a national community sample of 6755 participants (men = 3333, women = 3421).Results: Overall, prisoners were slightly more conservative in their attitudes towards sex than the community. They were more likely than the community to agree with the statement that abortion is wrong (men: adjusted odds ratio (AOR) = 3.3,95% confidence interval (CI): 2.8–3.9; women: AOR= 1.7, 95% CI: 1.2–2.4) and that male homosexuality is wrong (men: AOR= 2.6, 95% CI: 2.2–3.1; women: AOR= 1.7, 95% CI: 1.2–2.3); these differences were more pronounced for men than women. The attitudes of prisoners and the community varied with age. Attitudinal differences between prisoners and the community tended to be larger than the differences between women and men (agree that abortion is wrong: prisoners, AOR= 0.5, 95% CI: 0.4–0.7; community, AOR= 0.8, 95% CI: 0.7–0.9; agree that male homosexuality is wrong: prisoners, AOR= 0.4, 95% CI: 0.3–0.5; community, AOR= 0.6, 95% CI: 0.5–0.7). Conclusion: Prisoners have either similar or less accepting attitudes towards sex than the general population. These attitudes contrast with the higher engagement in risk behaviours reported by prisoners.